Carbon Nanotube Yarn‐Based Glucose Sensing Artificial Muscle. Issue 15 (1st March 2016) - Lee, Junghan; Ko, Sachan; Kwon, Cheong Hoon; Lima, Márcio D.; Baughman, Ray H.; Kim, Seon Jeong
Abstract : Boronic acid (BA), known to be a reversible glucose‐sensing material, is conjugated to a nanogel (NG) derived from hyaluronic acid biopolymer and used as a guest material for a carbon multiwalled nanotube (MWNT) yarn. By exploiting the swelling/deswelling of the NG that originates from the internal anionic charge changes resulting from BA binding to glucose, a NG MWNT yarn artificial muscle is obtained that provides reversible torsional actuation that can be used for glucose sensing. This actuator shows a short response time and high sensitivity (in the 5–100 × 10 −3 m range) for monitoring changes in glucose concentration in physiological buffer, without using any additional auxiliary substances or an electrical power source. It may be possible to apply the glucose‐sensing MWNT yarn muscles as implantable glucose sensors that automatically release drugs when needed or as an artificial pancreas. Abstract : A self‐powered glucose‐sensing artificial muscle is fabricated using a boronic acid‐conjugated hyaluronic acid nanogel guest in a two‐end‐tethered multiwalled nanotube yarn torsional actuator. This actuator shows continuous glucose level monitoring ability with high sensitivity and speed. This actuating sensor may be eventually used as a self‐powered actuating sensor that detects glucose level and responds to release appropriate drugs.